Graphene-bioactive glass composites: Structural, Vickers hardness, and gamma-ray attenuation characteristics - Deliormanli, Aylin M.; ALMisned, Ghada; Ene, Antoaneta; Tekin, H.O. (Frontiers in Materials, 2023)
Graphene-based materials have gained increasing attention for use in radiation attenuation applications. In this study, pristine graphene nanoplatelet-containing (1,3,5, and 10 wt.%) borate-based bioactive glass composites were prepared. Structural properties, Vickers microhardness, and gamma-ray radiation shielding properties of the fabricated composites were examined in detail. Results revealed that the inclusion of the graphene in the glass matrix led to a decrease in the bulk density of the glass-based composites. Similarly, a decrease in Vickers hardness was obtained as the graphene concentration was increased due to a convoluted effect of the non-uniform distribution of graphene nanoplatelets in the bioactive glass matrix and the higher residual porosity. On the other hand, the incorporation of graphene decreased the crack propagation after indentation which may be attributed to an increase in fracture toughness. The crack paths were not detectable for intended glass samples containing graphene starting from 3 wt.%. In the study, fundamental gamma ray absorption properties of graphene-containing bioactive glasses were examined in the 0.015 to 15 MeV incident photon energy range. For this purpose, the Py-MLBUF code was employed to determine gamma ray absorption parameters. Results showed that linear attenuation coefficients of the glass-based composites decreased due to a decrease in the density of the samples. On the other hand, as graphene was incorporated into the bioactive glass structure, EBF and EABF values increased. The growing graphene ratio in the glass structure contributed negatively to the photon's tendency to interact with the material.